Control of reinforcement concrete in pile caps over steel piles – Case study - Boni, Ricardo; Helene, Paulo (Revista ALCONPAT, 2020)
This paper presents a case study about the challenges and good building practices involved in the execution of structural reinforced concrete pile caps over steel piles. The structural reinforcements were carried out in a project with 3 residential towers of approximately 30 floors each, located on the seafront. As a result, it was observed that mix design to define the type and characteristics of concrete, prototype event, particularities of the construction site, executive procedures employed, as well as the systematic monitoring and control of concreting events and other constructive stages were determining factors to promote the safety and quality of reinforcement services in accordance with the assumptions and design requirements.